Effects of massage under hypoxic conditions on exercise-induced muscle damage and physical strain indices in professional soccer players - Gatterer, H.; Schenk, K.; Wille, M.; Murnig, P.; Burtscher, M. (Biology of Sport, 2013)
Reports based on experiences from masseurs and players, mostly without any scientific background, suggest that the combination of a classical regeneration method (i.e. massage) with exposure to hypoxia may enhance regeneration in soccer. The aim of this study was to evaluate whether this specific combination could affect blood parameters related to muscle damage and physical strain after a soccer game. Approximately 15 hours after two separate championship games, 10 professional male outfield players of the first Austrian division were exposed to normobaric hypoxia (FiO2 13.5% ~ 4000m) or normoxia for 1 hour (30 minutes rest followed by 30 min massage) (cross-over design). Creatine kinase (CK), urea and uric acid (UA) were measured 4 days before the first game, and 15 and 63 hours after the two games. Match play increased CK values independently of the intervention. No effect of the massage in combination with hypoxia was seen. A trend was found between delta UA ([UA] 48 hours after exposure minus [UA] before exposure) in response to hypoxia and SaO2 measured in hypoxia (r=0.612, p=0.06). Results show that massage under hypoxic conditions had no additional positive effect on the measured parameters compared to massage alone. Solely the trend of a relationship for delta UA and SaO2 might indicate that redox alterations are a potential consequence of hypoxic exposure.